2022
DOI: 10.1155/2022/1483665
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation for Development Effect of Enterprise Innovation with Neural Network from Low-Carbon Economy

Abstract: China has resolved to pay more and more attention to the sustainability of ecological construction and social development. The country has proposed a low-carbon economy policy; development and management of enterprises are also actively responding to the call for a low-carbon economy. Through a series of innovations and changes, it intends to realize its own low-carbon production and business development, thereby promoting transformation and optimization of industrial institutions. Innovation is a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Chaotic mapping strategy and opposition learning strategy were widely used in initial population. In the chaotic mapping strategy, Luo et al [21] have proposed tentline coupled chaotic mapping to initialize the population, which ensured that the GWO algorithm generated diverse populations; Another improved GWO algorithm used a two-dimensional chaotic map to initialize the population [22]; Zhao et al have generated GWO initial population through Chebyshev chaotic mapping, ensuring the diversity of the initial population and enhancing global search ability of GWO [36]; In addition, some studies have integrated chaotic maps; Xu et al have applied integrated mapping systems (CLS) to GWO to increase its population diversity and accelerate the convergence of the algorithm [37]. Besides chaotic mapping, the pseudo-antithesis number generation method based on opposition learning strategy was used to improve the distribution of population [38]; Another improved GWO also generate its opposition wolf by lens imaging learning strategy [39].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaotic mapping strategy and opposition learning strategy were widely used in initial population. In the chaotic mapping strategy, Luo et al [21] have proposed tentline coupled chaotic mapping to initialize the population, which ensured that the GWO algorithm generated diverse populations; Another improved GWO algorithm used a two-dimensional chaotic map to initialize the population [22]; Zhao et al have generated GWO initial population through Chebyshev chaotic mapping, ensuring the diversity of the initial population and enhancing global search ability of GWO [36]; In addition, some studies have integrated chaotic maps; Xu et al have applied integrated mapping systems (CLS) to GWO to increase its population diversity and accelerate the convergence of the algorithm [37]. Besides chaotic mapping, the pseudo-antithesis number generation method based on opposition learning strategy was used to improve the distribution of population [38]; Another improved GWO also generate its opposition wolf by lens imaging learning strategy [39].…”
Section: Related Workmentioning
confidence: 99%
“…However, different chaotic maps have different effects. To find the optimal value quickly, we analyzed and compared Sobol, Logistic, Iterative, and Circle maps [21,22] in Fig 1.…”
Section: Circle Population Initialization (Cgwo)mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the literature review and existing policy review, it is found that most of the low-carbon renovation policy documents on existing facilities are issued in 2022. However, the existing research mainly focuses on the evaluation of low-carbon renovation and the research on low-carbon emission reduction strategies of enterprises (Qu et al, 2021;Bai and Zhang, 2022;Jiang et al, 2020b;Dong et al, 2021). The research on the lowcarbon renovation of high-carbon emission enterprises has only begun to receive attention recently, and related research has begun to expand.…”
Section: Introductionmentioning
confidence: 99%